KRITERIA LAJUR SEPEDA MOTOR UNTUK RUAS JALAN ARTERI SEKUNDER - Muhammad Idris (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
ABSTRACT The high growth of motorcycle (M/C) with 23%-30% per year and the proportion of M/C with 50%- 73% particularly on secondary arterial road now days has given specific phenomenon to traffic situation of urban road. The most influencing growth predicted have increased the traffic accident and decreased level of road service. Actually, the M/C growth has not well services yet neither mean of existing facility nor traffic management. On the other side, the guidance which is needed for standardized development of M/C lanes has become a constraint for the road and traffic planner to solve the problems. Overall, the purposes of this study are to identify the performance indicators and criterions which are related to M/C lanes needs particularly on arterial urban road with 4/2 and 6/2 divided. This study was started with assumptions that the M/C growths have influenced to traffic performance. Several data have been collected and have analyzed by mean of traffic characteristic analyses (traffic volume and proportion, speed operational), Q/C analyses and M/C movement behavior analyses. The result analyses shows that the main criterion through the needs of M/C lanes M/C proportion ≥ 34,5% and M/C peak hour volume ≥ 1200 pcu’s. Statistical analyses also show that there were significant correlations of the two criterions with the degree of saturation Q/C > 0,65. Another criterion which is also important for M/C lanes designing was M/C accident proportion with greater than 40%. To design of LOS (level of service) D M/C lanes with 0,65≤Q/C<0,86 criterion this study suggested to use road marking as a lanes separator for inclusive M/C lanes and Q/C≥0,86 criterion for physical separator of exclusive M/C lanes. Furthermore, to design M/C lanes width for medium (M) side friction has proposed wider than 3,00 meter with M/C volume design greater than 625 pcu’s/hour and greater than 575pcu’s/hour for high (H) side friction with LOS C design. Keywords: performances indicator, M/C lanes criterion, M/C accident proportion, M/C volume and proportion, level of road services, road capacity, degree of saturation